Integrating Remote Monitoring Into the Pregnancy Care - Likitalo, Susanna; Pakarinen, Anni; Axelin, Anna (Lippincott, Williams & Wilkins, 2025)
Remote monitoring has been proposed to provide new opportunities to monitor pregnancy in the home environment and reduce the number of follow-up visits to the maternity clinic. Still, the integration of remote monitoring into the pregnancy care process has not been achieved. This descriptive qualitative study aimed to explore pregnant women’s and healthcare professionals’ perceptions of integrating remote monitoring into pregnancy monitoring process. A convenience sample of 10 pregnant women and 11 healthcare professionals participated in the focus group interviews. The data were analyzed with reflexive thematic analysis. The results comprised a four-step pregnancy monitoring process organizing the issues to consider when integrating remote monitoring into these steps. According to pregnant women and healthcare professionals, remote pregnancy monitoring should allow a holistic assessment to ensure the well-being of the pregnant woman and the fetus. Clear criteria for monitoring should guide the adaptation of monitoring to the identified monitoring needs. Ideally, remote monitoring could enable more personalized maternity care, supporting the monitoring-related decision-making of both pregnant women and healthcare professionals and facilitating the early detection of pregnancy complications. However, integration of remote monitoring would require significant restructuring of current pregnancy care processes.